Can ICT build a solid bridge to a more "engaged" and collaborative practice in doctoral study? Paradoxes, constraints and opportunities - Espinoza-Ramos, Rossana; Hammond, Michael (Proceedings of the International Conference on Networked Learning, 2008)
This paper is focused on a Teaching Quality funded project, begun in June 2006, to develop the use of ICT to support doctorate study, in particular to address a concern that there was insufficient sharing of resources and general communication between doctoral students, and also between supervisors and doctoral students. In addition, there was felt to be a more specific problem in that part-time students, at least those at a distance from Warwick, had difficulties in physically accessing research methods courses. The project looked, further, at whether ICT developments could sustain a shift to a more “engaged” and collaborative practice. This was an exploratory study, conducted within an action research approach, with cycles of reconnaissance, design and implementation, and evaluation leading to further developments. The reconnaissance provided the background and orientation to the project. It was found that doctoral students regarded collaboration very highly but many did not take advantage of the opportunities to meet with other doctoral students. It was also found that students made widespread use of ICT to access material but much less use to communicate with peers. Email use was centred on exchanges with the supervisor. Doctoral students used ICT purposefully, but not as so called 'digital natives'. They did not own the language of technology or see it as central to their lives. Hence the first round of implementation focused on the development of a website with material such as: research training material; seminar resources; upgrade support; Graduate Association projects; and study skills support. Overall, the development of the website was well-received, and attracted attention and raised expectations. However, it has not addressed head-on a prevailing culture that often leads to habits of independent study, rather than community. Here an incremental approach to change needs to be undertaken. The next round of developments will focus on networking and sharing knowledge. E-Portfolios are being developed as a departmental initiative with the hope this will help foster networking amongst doctoral students and engagement towards the further use of ICT. Another initiative revamping discussion forums. However, ICT developments are seen as only aspect of a wider picture in which collaboration is being encouraged.